Comparison of MDCT, MRI and MRI with diffusion-weighted imaging in evaluation of focal renal lesions: The defender, challenger, and winner! - Goyal, Ankur; Sharma, Raju; Bhalla, Ashu S; Gamanagatti, Shivanand; Seth, Amlesh (Indian Journal of Radiology and Imaging, 2018)
Purpose: To compare the diagnostic performance of multidetector computed tomography (MDCT), magnetic resonance imaging (MRI), and MRI with diffusion-weighted imaging (DWI) in the characterization of focal renal lesions. We also compared MDCT and MRI in the staging of renal cell carcinoma (RCC). Materials and Methods: One hundred and twenty adult patients underwent MDCT (40-row and 128-row scanners), MRI (at 1.5 T), and DWI (at b-values of 0 and 500 s/mm2) for characterization of 225 renal lesions. There were 65 malignant neoplasms (44 RCCs), 25 benign neoplasms, 25 abscesses, 45 pseudotumors, 15 hemorrhagic cysts, and 50 benign cysts. A composite gold standard including histology, typical imaging criteria, and follow-up imaging was employed. To determine the diagnostic performance of imaging modalities, area-under-curve (AUC) was calculated by receiver-operating-characteristic analysis and compared. Fisher’s exact test was used to compare the diagnostic accuracies and confidence levels with MDCT, MRI, and MRI + DWI. Cross-tabulation was used to assess the precision of MDCT and MRI in RCC staging. Results: AUC for MDCT (0.834) and MRI (0.841) in the classification of benign and malignant lesions were within corresponding 95% confidence interval (CI) (P = 0.88) whereas MRI + DWI had significantly better performance (AUC 0.968, P = 0.0002 and 0.0004, respectively). Both CT and MRI had low specificity (66.9% and 68.8%, respectively), which increased substantially with DWI (93.8%) owing to correct diagnosis of pseudotumors. MRI was superior to CT in diagnosing necrotic RCC and hemorrhagic cysts. MRI + DWI had the highest accuracy (94.2%) in assigning the definitive diagnosis and 97.6% lesions were diagnosed with very high confidence, significantly better than CT and MRI. Both CT and MRI had the same accuracy (86.1%) in RCC staging and evaluation of intravascular thrombi. Conclusions: Characterization of renal lesions was most accurate with MRI + DWI. The latter is also the most suitable modality in diagnosing pseudotumors and evaluating patients with renal dysfunction. CT and MRI were equivalent in RCC staging.
Keywords: Contrast media; diffusion-weighted MRI; focal renal lesion; MRI; multidetector CT; renal cell carcinoma